Defining clinical diagnosis and treatment of puerperal metritis in dairy cows: A scoping review - Adriana Garzon; Gregory Habing; Fabio Lima; Noelia Silva-del-Rio; Festus Samah; Richard Pereira (Journal of Dairy Science, 2022)
ABSTRACT: Although puerperal metritis (PM) is a common infectious disease in dairy cattle, there are currently discrepancies between clinical case definitions within and between available peer-reviewed literature and on-farms practices. The inconsistent use of PM criteria across studies and on-farms practices can result in disparities related to recommendations for treating cows, affecting judicious use of antimicrobials. The objective of this study was to systematically review the peer-reviewed literature for clinical signs used for case definition of PM. The criteria used included local (e.g., vaginal discharge) and systemic clinical signs of infection (e.g., fever, drop in milk). The Preferred Reporting Items for Systematic Review and Meta-Analysis extension for scoping reviews protocols were used to screen commonly used databases. Following this protocol, one reviewer screened title and abstract for eligibility (n = 2,096), followed by full-text screening of selected articles (n = 396) by 2 reviewers to confirm eligible articles (n = 174). The most frequently cited reference article (37.5%) for the definition of PM was published in 2006, followed by articles published between 1998 and 2009 (13%). In 40.2% of articles, no reference was provided for definition of PM; vaginal discharge was described in terms of color, odor, and viscosity when related to the PM definition. Terms used for description of vaginal discharge color were red-brown (61.4%), red (5.1%), brown (8.6%), chocolate (4%), white (1.7%), yellow (0.5%), pink (5.7%), or gray (0.5%); vaginal discharge color was not reported in 24.1% articles. The vaginal discharge odor was described as fetid (75.8%), putrid (5.1%), foul (10.3%), or other (5.7%; e.g., abnormal, malodorous, odoriferous); odor was not mentioned in 7.4% of articles. The vaginal discharge viscosity was described as watery (74.1%), purulent (27%), mucopurulent (8.6%), thin (4%), serous (2.8%), or abnormal (2.3%) and was not mentioned in 11.5% of articles. Fever was included in 59.7% of articles as a criterion for PM diagnosis. The most used rectal temperature threshold was ≥39.5°C (56.8%), followed by ≥39.2°C (2.8%). Approaches used for vaginal discharge evaluation included rectal palpation (37.3%), intravaginal exploration with a gloved hand (18.4%), Metricheck (9.8%), or speculum (5.7%); and in 28.7% of articles, diagnostic tools used were not mentioned. Many of the color and odor vaginal discharge descriptions observed in the literature, used synonymous words to describe the same vaginal discharge sample, highlighting a lack of terminology consensus that could result in disagreements, especially due to the subjective character of these clinical evaluations of vaginal discharge color and odor. Although select consensus articles are available, it is common for studies to disregard a reference when defining PM cases. Furthermore, our findings highlight the need for a robust and clear consensus on criteria and terminology used to diagnose PM.